Molecular Mechanism of Tinospora crispa on Herb-Drug Interaction in Rat Hepatocytes - T.P, Tin; C.K, Lam; A. Hj, Hussin (Malaysian Journal of Science, 2005)
Tinospora crispa (Family: Menispermaceae) has been used locally as a folk medicine for diabetes mellitus. The objective of this study is to elucidate the effects of T. crispa on the molecular mechanism of aminopyrine metabolism in rat hepatocytes. A total of two inhibitors of the second messenger system, namely IBMX and KT-5720 were investigated on the possible pathway that could mediate the effects of T. crispa on hepatic Phase I metabolizing enzymes. Normal old male Sprague Dawley rats (n = 6) were used in this study. Isolated hepatocytes cells were prepared using liver perfusion technique [1]. The effect of T. crispa on aminopyrine N-demethylase activity was determined in the absence or presence of inhibitors by measuring the quantity of formaldehyde formed using the method of Nash [2]. The findings showed that T. crispa may act via the cAMP pathway at lower concentrations, ranging from 1.0, 10, and 100 ng/ml, but gave paradoxical results at higher concentrations (0.001 - 1.0 mg/ml).